LA NATURALEZA EN GRAZIELLA DE LAMARTINE - Martínez Cuadrado, Jerónimo (Anales de Filología Francesa, 2006)
This paper touches carefully upon the romantic tale “Graziella” of Lamartine, by highlighting its peculiar subject matter as well as the numerous fragments in which nature appears. Sometimes nature shows itself as the very framework of the action –for instance, the night, a romantic element par excellence-. And in other cases the rural simplicity is described as a token of admiration for the life in a village. Indeed, the south of Italy and the Gulf of Naples of that period, with their exotic and colourful note, are the ideal framework for this beautiful story.